Targeting interleukin-20 alleviates paclitaxel-induced peripheral neuropathy. Issue 6 (June 2020) - Chen, Li-Hsien; Yeh, Yu-Min; Chen, Yi-Fan; Hsu, Yu-Hsiang; Wang, Hsiao-Hsuan; Lin, Peng-Chan; Chang, Lian-Yun; Lin, Chou-Ching K.; Chang, Ming-Shi; Shen, Meng-Ru
Abstract : Abstract: The role of immune mediators, including proinflammatory cytokines in chemotherapy-induced peripheral neuropathy (CIPN), remains unclear. Here, we studied the contribution of interleukin-20 (IL-20) to the development of paclitaxel-induced peripheral neuropathy. Increased serum levels of IL-20 in cancer patients with chemotherapy were accompanied by increased CIPN risk. In mouse models, proinflammatory IL-20 levels in serum and dorsal root ganglia fluctuated with paclitaxel treatment. Blocking IL-20 with the neutralizing antibody or genetic deletion of its receptors prevented CIPN, alleviated peripheral nerve damage, and dampened inflammatory responses, including macrophage infiltration and cytokine release. Mechanistically, paclitaxel upregulated IL-20 through dysregulated Ca 2+ homeostasis, which augmented chemotherapy-induced neurotoxicity. Importantly, IL-20 suppression did not alter paclitaxel efficacy on cancer treatment both in vitro and in vivo. Together, targeting IL-20 ameliorates paclitaxel-induced peripheral neuropathy by suppressing neuroinflammation and restoring Ca 2+ homeostasis. Therefore, the anti-IL-20 monoclonal antibody is a promising therapeutic for the prevention and treatment of paclitaxel-induced neuropathy. Abstract : Supplemental Digital Content is Available in the Text.Blocking IL-20–induced signaling can suppress neuroinflammation and restore calcium homeostasis to alleviate paclitaxel-induced peripheral neuropathy, which does not affect chemotherapy efficacy in vivo.